The effect of apelin-13 on memory of scopolamine-treated rats and accumulation of amyloid-beta plaques in the hippocampus - Maryam Azhir; Sara Gazmeh; Leila Elyasi; Mehrdad Jahanshahi; Behnaz Bazrafshan (Golestan University Of Medical Sciences, 2023)
Background: Neurodegenerative diseases (NDDs) cause progressive neuronal loss, resulting in morbidity and mortality. Research is continued on treatment strategies that can tackle the disease's pathophysiology and cease its progression. Considering the anti-apoptotic and neuroprotective properties of apelin, we hypothesized that apelin-13 could be a therapeutic solution for Alzheimer's disease and similar NDDs. Therefore, we evaluated its effect on scopolamine-treated rats. Methods: Male rats (n=40) were assigned to 5 groups of 8. No intervention was considered for the control group. The scopolamine group received stereotaxic surgery and was treated with 3 mg/kg scopolamine intraperitoneally. The treatment groups were treated with scopolamine plus intraventricular injection of apelin-13 (1.25, 2.5, and 5 µg) into the right lateral ventricles for 7 days. For evaluating the memory impairment, the passive avoidance reactions of the animals, except the control group, were assessed 24 hours following the last injection. Regarding histological analysis, Congo red staining of the hippocampal sections was done, and immunoblotting was used to determine apoptotic biochemical markers, including caspase 3, cytochrome C, and congophilic amyloid-beta plaques. Results: Apelin-13 alleviated scopolamine-related passive avoidance memory impairment and reduced the number of congophilic amyloid-beta plaques in the hippocampus (all P<0.001). It attenuated the decrease in the mean levels of hippocampal apoptotic proteins (caspase 3, cytochrome C) in animals treated with scopolamine (all P<0.05). Conclusion: The neuroprotective effects of apelin-13 suggest its therapeutic effect on neurodegenerative disorders.